Terminology Is A Tool In Development Of Lexical Competence - Bakirova Hilolahon Botiraliyevna (Genius Publishing Group, 2022)
The article considers about the role of terms of professionality in development of lexical competence in teaching English in technical universities. Teaching terminological vocabulary in foreign language classes aimed at special purposes is one of the most important tasks in the formation of professional communicative competence of future engineering students.
Keywords: role of terms; terms of professionality; lexical competence; communicative competence